Determinants of Accounting Student Career Interest in Sharia Financial Institutions - Lestari, Puji (Islamic Economic Scholar Association and Faculty of Economics and Business Universitas Jenderal Soedirman, 2023)
The purpose of this study is to identify the factors that influence students' desire in working for Islamic financial organizations. The population included undergraduates from Jenderal Soedirman University's accounting department as well as those from Muhammadiyah University Purwokerto, Wijayakusuma University Purwokerto, Nahdlatul Ulama University Purwokerto, and Saifuddin Zuhri State Islamic University Purwokerto's Sharia Banking department. These individuals were either present or prospective students of Sharia accounting courses. There were 93 students who fit the criteria and fully completed the disseminated questionnaire using the convenience sample approach. SPSS software version 25 was used to process and analyze the data. According to the study's findings, knowledge of Islamic accounting, religiosity, and gender have no effect on students' interest in careers in sharia financial institutions. Knowledge of Islamic accounting has a positive effect on students' interest in careers in sharia financial institutions.